Pengaruh Pesan Kampanye Peringatan Bahaya Rokok terhadap Niat Berhenti Merokok pada Perokok Aktif Mahasiswa Fikom UNPAD: (Studi Kuantitatif pada Mahasiswa Fakultas Ilmu Komunikasi Universitas Padjadjaran Strata 1 Angkatan 2021 dan 2022 Kampus Jatinangor) - Rafi Fathurrahman Fathoni; Dadang Sugiana; Putri Trulline (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Background: This research is motivated by the high prevalence of smoking among students, necessitating effective interventions. The research problem is whether there is a significant influence of anti-smoking campaign messages on the intention to quit smoking among active smokers in FIKOM Unpad. Purpose: The purpose of this study is to determine the influence of anti-smoking campaign messages, as well as the influence of attitudes, subjective norms, and behavioral control on the intention to quit smoking among active smokers in FIKOM Unpad. Methods: This study uses a quantitative approach with a survey method through questionnaires distributed to 120 respondents who are active smokers among FIKOM Unpad students. Data were analyzed using the coefficient of determination test and the T-test to measure the significance of the influence of these variables. Results: The results of the study show that anti-smoking campaign messages have a significant influence on the intention to quit smoking. Additionally, attitudes, subjective norms, and behavioral control also have a significant influence on the intention to quit smoking. The conclusion of this research is that anti-smoking campaign messages are effective in increasing the intention to quit smoking among active smokers in FIKOM Unpad. This research provides an important contribution to the development of effective health communication strategies through campaign messages.